(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Plant calli culture could be used as a source of genetic changes (somaclonal variation). There are known several flax varieties, bred on the basis of somaclonal variation, with improved resistance to biotic and abiotic stresses, plant height, seed yield and other traits. This method is useful for obtaining the new initial material for flax breeding, including for intensification of breeding for organic farming. Goal of the study was to obtain plants-regenerants from the calli culture of the fibre flax variety ‘Vega 2’ and to evaluate their agronomical traits and resistance to powdery mildew. For obtaining plants-regenerants was used early elaborated protocol of somatic calli cultivation. Agronomically important traits, such as total and technical plant height, number of seed vessels, number of seeds in a seed vessel, and resistance to diseases were evaluated. Most of somaclonal families had higher total and technical plant height in comparison with the initial variety ‘Vega 2’. In the opposite, number of seed vessels and number of seeds in a seed vessel had a tendency to decrease. It was concluded that even changes in not desirable direction may be recognised as an indirect indicator of the rather high level of induced somaclonal variation, which can occurred also in traits, which were not evaluated during this experiment, therefore there is a potential to exploit flax somaclonal variation in applied breeding programs as an additional source of variability.